Upstream. Intermediate B2: Workbook Student's - Evans V. Virginia (Newbury, Express Publishing, 2009)
Upstream Intermediate B2 is a modular secondary-level course for learners of the English language at post-intermediate level (Pre-FCE, CEF level B2, ALTE A3/A4 or any other examinations at the same level of difficulty.) The series combines active English learning with a variety of lively topics presented in themed units.Key Features theme-based units from a wide variety of sources in five modules a variety of cross-cultural topics systematic development of all four language skills through realistic challenging tasks which encourage the learner's personal engagement lexical exercises practising and activating all essential vocabulary including collocations, idioms, phrasal verbs and word formation a variety of authentic stimulating reading and listening tasks realistic, stimulating dialogues featuring people in everyday situations grammar sections covering all major grammatical areas plus a Grammar Reference Section composition analysis and practice on all types of writing with full models a wide range of speaking activities intonation & pronunciation sections Culture Clips Literature pages